Sistem Pendukung Keputusan Penentuan Siswa Magang Terbaik Menggunakan Metode Simple Additive Weighting SAW - I Komang Sugiartha; Eka Fitri Rahayu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Selecting the best interns is a crucial activity in assessing the success of the internship program at Budi Darma University. The manual assessment process often leads to subjectivity and is time-consuming. Therefore, a system capable of assisting in objective and efficient decision-making is needed. This study aims to develop a Decision Support System (DSS) for determining the best interns using the Simple Additive Weighting (SAW) method. The SAW method was chosen because it provides accurate results by summing the weighted scores of each alternative based on predetermined criteria. The assessment criteria used in this study include discipline, responsibility, communication skills, cooperation, and internship report results. Assessment data is processed by weighting each criterion, then calculated using the SAW formula to obtain each student's preference score. The results show that the system can assist the university in quickly and objectively determining the best interns. This system makes the assessment process more transparent, accurate, and supports data-driven decision-making.